ANALISIS PRODUKTIVITAS, PENDAPATAN DAN KESEJAHTERAAN PETANI KARET EKS UPP TCSDP DI DESA SEMELINANG DARAT KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Atika, Siti Nurul; Dewi, Novia; Rifai, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aims to analyze the productivity, the revenue, the households income structure, the pattern of households expenditure, and the welfare of households of the smallholder rubber plantation of ex-TCSDP development. Research was done by survey at Semelinang Darat Village. Data were collected from 30 small-holders rubber farmers using purposive sampling technique. Analysis of the results showed that the productivity of smallholder rubber plantation as 2.79 ton/ha/year, the revenues of smallholder rubber plantation as Rp 6.466.065/ha/year. The structure of household income derived from agriculture is 85,07 percent and 14,93 percent for non-agricultural income. The pattern of household expenditure shown that the food expenditure as 32,36 percent and non-food expenditures as 67,64 percent. Result also show that the household of the smallholder rubber plantation at Semelinang Darat Village have the total expenditure more than 240 kg of rice equivalent. The household of small-holders rubber plantation have the total expenditure above the poverty line (Rp 369.210 /capita/month). The household welfare using the 14 indicators of relative poverty by Indonesian Statistic show that 83,33 percent household have ability to fullfill the basic need or prosperous, while 16,67 percent is almost prosperous. Key words : Rubber Farmer, Productivity, Income, Welfare